Internationalization of Neo-Nazism and Social Media: Psychosocial, Sociopolitical and Security Inquiry - Faruk Hadžić (Lectio Socialis)

(untitled)
This research analyses the internationalization paradigm of extremism and neo-Nazism, affecting related global events within the historical, psychosocial, sociopolitical, security, and globalized media framework; problematizing a gap between peace, violence, democratic legislation, social awareness, political agendas, participation, and hyperpersonal communication theories. The radicalization process can be initiated or encouraged by sociopolitical or sociopsychological circumstances that directly or indirectly affect the individual. There is no detailed profile of a person attentive to commit terrorism, various positions, and judgments. The capacity and participation in the sociopolitical process are questioned. The impoverishment of public life and the public sphere creates a critical potential for demagogic and ideological extremist manipulation. Democratic accountability and transparency could be submerged by far-right spin specialists who have more scope to manage information. Such an occurrence coincides with the mass society theories. Hyperpersonal communication initiated securitization, highlighting the internationalization of neo-Nazism and neo-Fascism (i.e., Norwegian-Breivik and New Zealand-Tarrant). It is undeniably essential that a democratic, legal state has a monopoly on violence. The lack of decision-makers in the political sphere who would: establish a different direction in the constitution of the community, understanding that managing the relevant weaponry and cognate laws is a regional, transnational, and trans-party issue, and the actual field of their political legitimacy; a failure for diverse global societies.